Prevalence of sexual violence: A comparison of estimates from UK national surveys - Brunton-Smith, Ian (European journal of criminology, 2022)
Accurately measuring the prevalence of sexual violence is difficult. Police-recorded crime figures are known to underestimate the true extent of sexual violence, and so researchers have tended to rely on survey estimates instead. But estimates from surveys are not uniform, with recent estimates from the UK National Survey of Sexual Attitudes and Lifestyles apparently twice as large as official figures from the major crime surveys (the Crime Survey for England and Wales and the Scottish Crime and Justice Survey). In this study we use harmonized data from these three surveys and the UK component of the EU Violence Against Women Survey to explore the features of the surveys that may have contributed to these differences.